Assessment of Thalassia hemprichii seagrass metrics for biomonitoring of environmental status. Issue 1 (January 2020) - Zulfikar, A; Boer, M; Adrianto, L; Puspasari, R
Abstract: Seagrass has long been known to be very sensitive to environmental changes, especially caused by human activities and has been used as a bioindicator for environmental condition of ecosystems. This research aimed to study 19 Thalassia hemprichii metrics (10 measured and 9 derived metrics) at two organizational levels (individual and population), to explore and confirm these metrics for development of a multimetric index of environmental quality. Seagrass meadows was selected along a gradient of an anthropogenic disturbance at Kepulauan Seribu (inhabited and uninhabited locations, fixed effect, namedly Status), 4 sites for each location (random effect nested in status) within intertidal and subtidal zones (random effect across Sites). We also briefly described about social-ecological system of seagrass being studied using a qualitative network model, for an understanding of interaction that affects the exploited seagrass ecosystems. The significance of variability between states, sites, and zones were examined using linear mixed effect model followed by exploratory factor analysis in the confirmatory factor analysis (CFA) framework (E/CFA strategy) to explore and confirm adequacy of the metrics as indicators for two-factor organizational levels (individual and population). Based on the analysis, leaf surface area, leaf wide, leaf area index, density, rhizome diameter, and Thalassia hemprichii cover differed significantly at the scale of interest and represented two levels of organizational levels (individual and population).